Avaliação da rigidez arterial e pressão aórtica central em pacientes hipertensos resistentes - Mendes, Alessandra Beatriz Balduino (2015)
Background: Hypertension Resistant (RH) is defined as office blood pressure (BP) ≥140 / 90 mmHg in patients using at least three antihypertensive classes at optimal doses, including a diuretic. Arterial stiffness is a major manifestation of RH, a determining fator, for increasing central pressure and pulse pressure. Arterial stiffness can be measured by three parameters: the central arterial pressure (CAP), augmentation index (AIx) and pulse wave velocity (PWV). These parameters can be estimated by simple methods, non-invasive and with high sensitivity, such as tonometry or 24-hour ambulatory blood pressure monitoring (ABPM). Objectives: To study and compare the anthropometric, biochemical profile and central hemodynamic values (CAP, AIx and PWV) by 24-hour ABPM in patients resistant hypertension (RH), controlled hypertensive (CH) and normotensive (NT). Methodology: We selected 59 patients with resistant hypertension, 62 controlled hypertensive and 60 normotensive, all submitted to ABPM. The level of significance was accepted for P-value <0.05. Results: Individuals CH and RH group presented higher mean age and higher body mass index (60.4; 60.2 years and 29.6; 29.7 kg/m2, respectively) compared to the NT group (53.2 years and 26.2 kg/m2) (P <0.05). RH showed higher levels of creatinine and decreased renal function (1.1 mg/dL and 67.3mL/min/m2) compared to CH (0.9 mg/dL and 79.3mL/min/m2, P <0.05) and NT (0.8 mg/dl and 85.3mL/min/m 2; P <0.05). Glucose and uric acid were higher and HDL-C lower in the RH group compared to CH and NT, but without statistical significance. Systolic blood pressure (SBP) and diastolic pressure (DBP) of office were significantly higher in the RH group (137.1/80.7mmHg) compared to CH (124.3/74.0mmHg) and NT (117.5/74.3mmHg). SBP and DBP in the 24-hour ABPM in daytime and night were higher in RH (129.4/78.9, 130/80 and 128.3/76.9mmHg, respectively) compared to CH (119.4/72.7; 121.3/75.0 and 115.7/68.3mmHg, respectively) and NT (114.8/71.8, 117.8/74.8 and 109.3/66.4mmHg, respectively). Heart rate (HR) and pulse pressure (PP) were significantly higher in RH (72.4bpm/min and 52.2mmHg, respectively) than in groups CH (67.5bpm/min and 47.2mmHg, respectively) and NT (67.3bpm/min and 42.9mmHg, respectively) during the sleep period. RH showed less nocturnal than CH and NT (P <0.05). SBP and DBP in the 24-hour ABPM in daytime and night were significantly higher in RH (119.2, 118.8 and 119.8mmHg, respectively) compared to CH (110.4, 111.5 and 109mmHg, respectively) and NT (107.2; 109.2 and 104.2mmHg, respectively). PWV was higher in RH compared to CH and NT diring the three periods assessed, although there was no statistical significance. The AIx values did not differ among the three groups in all periods. In RH, age and PWV were significantly associated to the CAP. There was a positive correlation between central SBP and PP and between central SBP and PWV in the RH group. Conclusion: The patients with resistant hypertension presented CAP_ higher level than the ones with controlled hypertensive and normotensive; this clearly demonstrates a greater arterial stiffness and a growing cardiovascular risk.